Superexploração da força de trabalho e política sindical no Brasil - Duarte, Pedro Henrique Evangelista (2010)
Formulated within the theoretical-abstract issues of the marxist theory of dependency, the concept of workforce superexploration was directed to the comprehension of the mechanisms that, as a result of the income transference between peripheral and central countries in landmarks of the international business relations, allowed the continuation of the process of capital accumulation and reproduction in the peripheral and dependant economies, from the conjugation between the arose of the intensity of work and remuneration under the minimum amount necessary to guarante the reproduction capacity of the working class, while mechanisms which increase the surplus value. In concrete terms, the Brazilian working class, in the ends of 1970, reorganized its forms of militant organization, process which guided the creation of the Central Única dos Trabalhadores (CUT). Throughtout these aspects, the intention of the present work is linked to the analysis of the concrete relation between the workforce superexploration and the union politics adopted by the CUT since 1990. The central argument that guides the investigation lies on the fact that, through the implementation of the neoliberal politics, the work relations have gone in deep transformations, making not only the working class but also its representative institutions extremely fragile in respect to the government and the capitalist class. Therefore, the transformations in the work relations had not only created a more propitious context to the use of the mechanisms of workforce superexploration but, at the same time, they had pressured the CUT to adopt standard actions of labor union more moderate, therefore, less militant. Because of that, in an environment of work precarization, the representative role built by the CUT along its history has been disarticulated.